Evolution of 21st Century Sea Level Rise Projections. Issue 11 (25th November 2018) - Garner, Andra J.; Weiss, Jeremy L.; Parris, Adam; Kopp, Robert E.; Horton, Radley M.; Overpeck, Jonathan T.; Horton, Benjamin P.
Abstract: The modern era of scientific global‐mean sea level rise (SLR) projections began in the early 1980s. In subsequent decades, understanding of driving processes has improved, and new methodologies have been developed. Nonetheless, despite more than 70 studies, future SLR remains deeply uncertain. To facilitate understanding of the historical development of SLR projections and contextualize current projections, we have compiled a comprehensive database of 21st century global SLR projections. Although central estimates of 21st century global‐mean SLR have been relatively consistent, the range of projected SLR has varied greatly over time. Among studies providing multiple estimates, the range of upper projections shrank from 1.3–1.8 m during the 1980s to 0.6–0.9 m in 2007, before expanding again to 0.5–2.5 m since 2013. Upper projections of SLR from individual studies are generally higher than upper projections from the Intergovernmental Panel on Climate Change, potentially due to differing percentile bounds or a predisposition of consensus‐based approaches toward relatively conservative outcomes. Plain Language Summary: In spite of more than 35 years of research, and over 70 individual studies, the upper bound of future global‐mean sea level rise (SLR) remains deeply uncertain. In an effort to improve understanding of the history of the science behind projected SLR, we present and analyze the first comprehensive database of 21st century global‐mean SLR projections. Results show a reduction in the range of SLR projections from the first studies through the mid‐2000s that has since reversed. In addition, results from this work indicate a tendency for Intergovernmental Panel on Climate Change reports to err on the side of least drama —a conservative bias that could potentially impede risk management. Key Points: We present the first comprehensive database of 21st century global sea level rise projections Upper estimates of sea level rise in 2100 are often higher than upper bounds found in Intergovernmental Panel on Climate Change reports A comparison of recent global sea level rise projections reveals far greater agreement among studies in 2050 compared to 2100